Comparison of the causes of death and wounding patterns in urban firearm-related violence and civilian public mass shooting events. Issue 2 (February 2020) - Maghami, Sam; Hendrix, Cheralyn; Matecki, Mary; Mahendran, Karthika; Amdur, Richard; Mitchell, Roger; Diaz, Francisco; Estroff, Jordan; Smith, E. Reed; Shapiro, Geoff; Sarani, Babak
Abstract : BACKGROUND: There are no reports comparing wounding pattern in urban and public mass shooting events (CPMS). Because CPMS receive greater media coverage, there is a connation that the nature of wounding is more grave than daily urban gun violence. We hypothesize that the mechanism of death following urban gunshot wounds (GSWs) is the same as has been reported following CPMS. METHODS: Autopsy reports of all firearm-related deaths in Washington, DC were reviewed from January 1, 2016, to December 31, 2017. Demographic data, firearm type, number and anatomic location of GSWs, and organ(s) injured were abstracted. The organ injury resulting in death was noted. The results were compared with a previously published study of 19 CPMS events involving 213 victims. RESULTS: One hundred eighty-six urban autopsy reports were reviewed. There were 171 (92%) homicides and 13 (7%) suicides. Handguns were implicated in 180 (97%) events. One hundred eight (59%) gunshots were to the chest/upper back, 85 (46%) to the head, 77 (42%) to an extremity, and 71 (38%) to the abdomen/lower back. The leading mechanisms of death in both urban firearm violence and CPMS were injury to the brain, lung parenchyma, and heart. Fatal brain injury was more common in CPMS events as compared with urban events involving a handgun. CONCLUSION: There is little difference in wounding pattern between urban and CPMS firearm events. Based on the organs injured, rapid point of wounding care and transport to a trauma center remain the best options for mitigating death following all GSW events. LEVEL OF EVIDENCE: Epidemiological, level IV.